MULTIVARIATE ANALYSIS BETWEEN THE PHYTOCHEMICAL FEATURES AND ANTIOXIDANT PROPERTIES OF THE STEMS OF BAUHINIA GLABRA JACQ. (FABACEAE) - Campos, Ranieri; OLIVEIRA, VINICIUS BEDNARCZUK DE; PAULA, CRISTIANE DA SILVA; Pontarolo, Roberto; DIAS, JOSIANE DE FATIMA GASPARI; Miguel, Marilis Dallarmi; Zanin, Sandra Maria Warumby; Miguel, Obdulio Gomes (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: To provide information about the phytochemical features of the crude extract (CruE) and fractions of the forageBauhinia glabra Jacq., Fabaceae, and present themultivariate correlation between its metabolites and the antioxidant properties. Methods: Studies were carried out by extraction with ethanol, sequential partition with hexane, chloroform and ethyl acetate, determination of the total yield of extraction, qualitative and quantitative estimation of phytochemicals.Then, the evaluation of antioxidant properties by four methods: 1,1-diphenyl picrylhydrazyl free radical scavenging assay (DPPH), the reduction power, the evaluation of inhibition of lipid peroxidation (TBARS) and the evaluation of recovery of content of methemoglobin in erythrocytes. Results: Phytochemical analysis on CruErevealed the presence of chlorophylls, carotenoids, coumarins, phytosterols, anthocyanins, tannins and flavonoids. Quantitative estimation of metabolites on CruE showed high concentration of phytosterols (42.21±2.34) mg/gdw and total phenolic (58.50±1.98) mg/gdw. The best results onthe antioxidant properties on each assay were the chloroform fraction (ChlF) with 13.76±0.23 and methanolic fraction (MetF) with 13.46±0.45 of half-maximal inhibitory concentration (IC50) values (DPPH).The HexF(60.99±1.76%) and ChlF(64.40±1.73%), both based on reduction power of ascorbic acid. The HexF(73.54±2.74%) of inhibition of lipid peroxidation (TBARS), and HexFwith 7.28±0.36% amount of methemoglobin. Conclusion: Based on multivariate analysis, HexFthat presented the highest concentration of phytosterols, has the highest reduction power and was more effectivefor inhibition of lipid peroxidation and in recoveringmethemoglobincontent. Therefore, the mechanism of these activities seems to be related to the reduction power presented by phytosterols.